2009
DOI: 10.1186/1471-2458-9-333
|View full text |Cite
|
Sign up to set email alerts
|

Individual and contextual covariates of burnout: a cross-sectional nationwide study of French teachers

Abstract: Background: Limited information on the covariates of burnout syndrome in French teachers is available. The aim of this study was to evaluate the relative contributions of individual and contextual factors on the three burnout dimensions: emotional exhaustion, depersonalization, and reduced personal accomplishment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
65
0
24

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 48 publications
(55 reference statements)
6
65
0
24
Order By: Relevance
“…Work pressure or overload was significantly related to burnout, a finding that has been reported by others (41,42). In line with the findings of a French study (43), high number of students per class was significantly associated with burnout.…”
Section: Discussionsupporting
confidence: 88%
“…Work pressure or overload was significantly related to burnout, a finding that has been reported by others (41,42). In line with the findings of a French study (43), high number of students per class was significantly associated with burnout.…”
Section: Discussionsupporting
confidence: 88%
“…These are all facets of teaching that increasingly are becoming a part of teaching in schools in problem areas (Paulle 2005). Our findings can easily be related to the finding that contextual variables as teaching in an underprivileged area and number of pupils taught were both significantly related to emotional exhaustion (Vercambre et al 2009). They are also in line with findings from a multi-level analysis of 1939 teachers within 198 schools that showed that disciplinary problems at the school level were predictive of between school variability in emotional exhaustion (Klusmann et al 2008).…”
Section: _______________________supporting
confidence: 56%
“…Quando o número de clientes aumenta, também se elevam as demandas, e, se estas são mais contínuas do que intermitentes, o trabalhador pode ficar mais vulnerável ao Burnout (Cordes & Dougherty, 1993). No caso do professor, problemas na relação com os alunos são um dos principais preditores da SB (Otero et al, 2008;Pas, Bradshaw, Hershfeldt & Leaf, 2010;Rudow, 1999;Vercambre et al, 2009;Yong & Yue, 2008). Relacionada a essa questão, é apontada a falta de reciprocidade com os alunos (Bakker et al, 2000;Schaufeli, 2005), a ambigüidade, o conflito e a sobrecarga de papel (Farber, 1991;Konukman et al, 2010).…”
Section: Discussionunclassified